2019
DOI: 10.1111/cod.13213
|View full text |Cite
|
Sign up to set email alerts
|

Patch test reactivity to iodopropynyl butylcarbamate in consecutive patients during a period of 7 years

Abstract: DISCUSSIONThis relatively low reactivity to IPBC, and the higher prevalence in males and those aged >40 years, are consistent with results from another European centre, 7 but are distinct from results from the last 10 years in North America. They showed higher reactivity to IPBC (between 3.1% and 4.7%), possibly because of the inclusion of doubtful results and the higher patch test concentration (0.5% pet). 8 Low IPBC reactivity contrasts with high reactivity to isothiazolinones (>14%), 9 which is still found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
8
1
1
Order By: Relevance
“…However, other studies found a lower sensitization prevalence (eg, 0.53%). 57 IPBC liberates iodine, which has also been supported by observing simultaneous contact allergy to IPBC and iodine. 58 Owing to possible endocrine interference, use concentrations are restricted to between 0.02% in rinse-off products and 0.0075% in deodorants/antiperspirants for many years (SCCNFP/0826/04, EU Cosmetics Regulation, Annex V/56).…”
Section: Additional Consecutively Tested Allergensmentioning
confidence: 68%
See 1 more Smart Citation
“…However, other studies found a lower sensitization prevalence (eg, 0.53%). 57 IPBC liberates iodine, which has also been supported by observing simultaneous contact allergy to IPBC and iodine. 58 Owing to possible endocrine interference, use concentrations are restricted to between 0.02% in rinse-off products and 0.0075% in deodorants/antiperspirants for many years (SCCNFP/0826/04, EU Cosmetics Regulation, Annex V/56).…”
Section: Additional Consecutively Tested Allergensmentioning
confidence: 68%
“…Iodopropynyl butylcarbamate (IPBC) 0.2% pet., tested in more than 20 000 consecutive patients, caused over 1% positive, mostly weak positive, reactions and about three times as many doubtful or irritant reactions. However, other studies found a lower sensitization prevalence (eg, 0.53%) 57 . IPBC liberates iodine, which has also been supported by observing simultaneous contact allergy to IPBC and iodine 58 .…”
Section: Discussionmentioning
confidence: 85%
“…IPBC, patch tested 0.2% pet., is used as a preservative (mainly fungicide) in industrial applications, for example, wood protective agents, pulp in paper production, water‐based paints, or water‐based MWFs, 9,23,24 as well as in household products, cosmetics, and body care products. In earlier studies from 2000 to 2003, we found sensitization to IPBC in less than 1% of the metalworkers with OD who were tested with the metalworking series 7,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of iodopropynyl butylcarbamate (IPBC), it is iodine liberation and systemic availability that led the EU to limit the use concentration to 0.02% in rinse-off, 0.01% in leave-on cosmetics and 0.0075% in deodorants, see (EC) No 1223/2009. The recent observation of frequent concomitant allergic reactions to IPBC and iodine [340] supports this cautionary approach, pointing to a relevant co-exposure to both IPBC, which is a contact allergen in its own right [341], and (liberated) iodine.…”
Section: Allergen-specific Aspectsmentioning
confidence: 97%